Exploring Digital Maturity Perception vs. Reality in Hungarian SMEs - Péntek, Ádám; Kovács, Sándor; Helmeczi, András; Kovács, Tamás (Economica, 2025)
The research aimed to explore how the digitalization development of micro, small, and medium-sized enterprises (SMEs) in Hungary relates to their perceived digital readiness, and what role the size of the enterprise plays in this relationship. During the data collection, structured questionnaire data were collected from 207 enterprises, which were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The reliability of the measurement model was adequate (Cronbach alpha: 0.728–0.915; AVE: 0.579–0.792), and the discriminatory validity was verified by several procedures (e.g., HTMT values: 0.425–0.641). According to the results of the structural model, actual digitalisation had a negative, significant relationship with perceived digital readiness (β = -0.444; p < 0.001) and perceived adaptability (β = -0.501; p < 0.001). The size of the enterprise also had a significant impact on the perception of adaptability (β = 0.363; p < 0.001) and also played an intermediary role in the model. The results suggest that more advanced businesses are more critical of their situation, while smaller companies tend to overestimate their digital capabilities. The research contributes to a deeper understanding of the distortions of digitalization self-assessment and the foundation of targeted development interventions.